PENGARUH MEDIA INTRANET TERHADAP KINERJA KARYAWAN PADA PT. TELEKOMUNIKASI INDONESIA WITEL RIAU DARATAN - Muhammad Panji Putra Irwan; Evawani Elysa Lubis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
PT Telkom Indonesia (Persero) Tbk is a State-Owned Enterprise (BUMN) which is engaged in telecommunications networks and services, information technology (ICT) and Indonesian telecommunications networks., PT Telkom Indonesia is the largest telecommunications company in Indonesia with 7 regional offices, 61 regions telecommunications (Witel), 422 Telkom plaza outlets, 11 Global offices overseas (Singapore, Hong Kong, Timor Leste, Australia, Malaysia, Macau, Thailand, United States of America, Myanmar, Saudi Arabia and New Zealand. This type of research is an explanatory quantitative research, the sample in this study is the employees of PT. Telekomunikasi Indonesia Witel Riau Mainland, totaling 100 people, was obtained by means of a census or taking all of them. The data obtained using a questionnaire distributed to consumers of PT. Telekomunikasi Indonesia Witel Riau Mainland was then tested with SPSS version 25 software for windows.The results of hypothesis testing in this study using simple linear regression analysis obtained the results of intranet (X) = (20.274) with T-table 100 = (1.984). It is known that (X) > T-table (20.274 > 1.984) it can be concluded that each independent variable affects the dependent variable because T-count > T-table. Then H0 is rejected and Ha is accepted. The results of research on the effect of intranet on employee performance at PT. Telekomunikasi Indonesia Witel Riau Mainland has a coefficient of determination (R2) of (0.807). This figure provides an understanding that the effect of Variable independent (Intranet) on Variable dependent (Employee Performance) is (80.7%). If interpreted, then the coefficient value is in the category of very strong influence. Thus, the effect of Variable independent (Intranet) on Variable dependent (employee performance) is 80.7% with a very strong category, while the remaining (19.3%) is influenced by other factors outside of the results obtained.